2023
DOI: 10.3390/ijms24087505
|View full text |Cite
|
Sign up to set email alerts
|

SAA1 Has Potential as a Prognostic Biomarker Correlated with Cell Proliferation, Migration, and an Indicator for Immune Infiltration of Tumor Microenvironment in Clear Cell Renal Cell Carcinoma

Abstract: The tumor microenvironment (TME) plays an important part in the initiation and development of clear cell renal cell carcinoma (ccRCC). However, an understanding of the immune infiltration in TME is still unknown. Our study aims to explore the correlation between the TME and the clinical features, as well as the prognosis of ccRCC. In the present study, ESTIMATE and CIBERSORT computational methods were applied to calculate the proportion of tumor-infiltrating immune cells (TICs) and the amount of immune and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Cell adhesion/migration-related pathways and immune-related pathways were significantly enriched in both gene sets. Previous studies have also identified the close association between SAA1 and tumor metastasis 43 , 44 . Nevertheless, no study has yet elucidated the plausible regulatory connection between MMP and SAA1 in ccRCC.…”
Section: Discussionmentioning
confidence: 82%
“…Cell adhesion/migration-related pathways and immune-related pathways were significantly enriched in both gene sets. Previous studies have also identified the close association between SAA1 and tumor metastasis 43 , 44 . Nevertheless, no study has yet elucidated the plausible regulatory connection between MMP and SAA1 in ccRCC.…”
Section: Discussionmentioning
confidence: 82%